Capping protein beta is required for actin cytoskeleton organisation and cell migration during Drosophila oogenesis. - Ogienko, A.A.; Karagodin, D.A.; Lashina, V.V.; Baiborodin, S.I.; Omelina, E.S.; Baricheva, E.M. (Cell Biology International, 2013)
Capping protein (CP) is a well-characterised actin-binding protein important for regulation of actin filament (AF) assembly. CP caps the barbed end of AFs, inhibiting the addition and loss of actin monomers. In Drosophila melanogaster, the gene encoding CP ?-subunit is named capping protein beta (cpb; see Hopmann et al. [1996] J Cell Biol 133: 1293-305). The cpb level is reduced in the Drosophila bristle actin cytoskeleton and becomes disorganised with abnormal morphology. A reduced level of the CP protein in ovary results in disruption of oocyte determination, and disturbance of nurse cell (NC) cortical integrity and dumping. We describe novel defects appearing in cpb mutants during oogenesis, in which cpb plays an important role in border and centripetal follicle cell migration, ring canal development and cytoplasmic AF formation. The number of long cytoplasmic AFs was dramatically reduced in cpb hypomorphs and abnormal actin aggregates was seen on the inner side of NC membranes. A hypothesis to explain the formation of abnormal short-cut cytoplasmic AFs and actin aggregates in the cpb mutant NCs was proffered, along with a discussion of the reasons for 'dumpless' phenotype formation in the mutants.